Pregnant women of South Asian ethnicity in Canada have substantially lower vitamin B12 status compared with pregnant women of European ethnicity. Issue 6 (18th September 2017) - Schroder, Theresa H.; Sinclair, Graham; Mattman, Andre; Jung, Benjamin; Barr, Susan I.; Vallance, Hilary D.; Lamers, Yvonne
Abstract: Maternal vitamin B12 (B12 ) status has been inversely associated with adverse pregnancy outcomes and positively with fetal growth and infant development. South Asians, Canada's largest ethnic minority, are prone to B12 deficiency. Yet, data are lacking on B12 status in South Asian pregnant women in North America. We sought to determine B12 status, using multiple biomarkers, in 1st and 2nd trimester pregnant women of South Asian and, for comparison, European ethnicity living in Vancouver, Canada. In this retrospective cohort study, total B12, holotranscobalamin (holoTC), methylmalonic acid (MMA), and total homocysteine concentrations were quantified in two routinely collected (mean gestational week: 11·5 (range 8·3–13·9) and 16·5 (range 14·9–20·9)), banked serum samples of 748 healthy pregnant South Asian ( n 371) and European ( n 377) women. South Asian pregnant women had significantly lower B12 status than European pregnant women at both time points, as indicated by lower serum total B12 and holoTC concentrations, and higher MMA concentrations (all P ≤0·001). The largest difference, which was substantial (Cohen's d ≥0·5), was observed in mean serum total B12 concentrations (1st trimester: 189 (95 % CI 180, 199) v . 246 (95 % CI 236, 257) pmol/l; 2nd trimester: 176 (95 % CI 168, 185) v . 226 (95 % CI 216, 236) pmol/l). Further, South Asian ethnicity was a significant negative predictor of B12 status during pregnancy. South Asian women living in Vancouver have substantially lower B12 status during early pregnancy. Future research identifying predictors and health consequences of this observed difference is needed to allow for targeted interventions.